Study of adaptivity of children living in metropolis to physical activity - A V Martyshov (RUDN Journal of Ecology and Life Safety, 2013)
Article presents monitoring results of adaptive reactions of the students’ organisms. Reactions of organisms of children who are engaged in karate since age of 7—9 to physical and psychological stress are studied. It is shown that application of certain methodic may reduce incidence of disease and increase in level of academic performance. Positive dynamics of the children from experimental group on such indicators as level of physical fitness, physical development (growth), posture, level of emotional stability is shown. The study of psychophysiological adaptation of children to physical activity in metropolis showed relatively high ecologic-adaptive value of karate for children of primary school age.